Increasing the Economic Capacity of Fishing Communities produced by Malay Fisheries and Tanjak in Jaring Halus Village, Secanggang District, Langka Regency - Nurman Ginting; Syaiful Amri Saragih; Muhammad Andi Prayogi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The aim of the Community Independence Program (PKM) activities in Jaring Halus Village, Kec. Secanggang District. Langkat, namely providing education about the character of entrepreneurship and exploiting the potential of fishing communities and Malay tanjak artisans in the village of Jaring Halus district. Secanggang by providing assistance training for Malay seriding and tanjak fish processing as well as digital marketing training. The activities that have been carried out by the service team with partners are efforts to increase creativity, innovation and productivity as well as increase economic capacity by fostering an entrepreneurial spirit through the processing of seriding seafood and the packaging of Tanjak Melayu. The results of the PKM activities obtained by the fishing community and Malay tanjak craftsmen in Jaring Halus village, include: Increased insight and knowledge of partners regarding the processing of marine products in the form of seriding and packaging of Tanjak Melayu, Improved science and technology (IPTEK) partners regarding business opportunities through the provision of Digital Marketing training, Increasing the economic capacity of fishing communities and Malay Tanjak craftsmen in the village of Jaring Halus.